Thermal stresses in two-dimensional model of composite elastic material - Wesołowski, Zbigniew (Computer Assisted Methods in Engineering and Science, 1994)
A rectangular specimen consists of two kinds of grains. Each kind has a different thermal expansion coefficient. The grains are randomly distributed in J rows and K colums of the specimen. The temperaturę of the whole specimen is increased and produces internal strains. It is assumed that each grain interacts with its four neighbours. The interaction force is proportional to the relative displacement. If the relative displacement equals the extension due to thermal expansion, the force equals zero. The relaxation method of calculating the equilibrium strains is used. The average maximum strains are calculated for a large number of numerical experiments. The standard deviations are calculated.